Formalisation and flexibilisation in dispute resolution - Zekoll, Joachim; Bälz, Moritz; Amelung, Iwo (Brill Nijhoff, 2014)
Formal law versus informal justice - these are two frequently invoked labels to highlight the distinction between court-based and 'alternative' dispute resolution (ADR). Indeed, it appears to be all but a truism to assume that ADR has developed as a more flexible and creative alternative to rigid and formalised judicial proceedings. In this book, scholars from four continents examine both historical and recent developments that cast doubt on the validity of these widespread assumptions. They not only explore trends towards an increased formalisation of ADR procedures but also address the tendencies of state civil justice systems to adopt flexible and informal tools for the resolution of disputes in the courts.